2013
DOI: 10.1016/j.resp.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mononuclear cell therapy in experimental allergic asthma: Intratracheal versus intravenous administration

Abstract: We hypothesized that the route of administration would impact the beneficial effects of bone marrow-derived mononuclear cell (BMDMC) therapy on the remodelling process of asthma. C57BL/6 mice were randomly assigned to two main groups. In the OVA group, mice were sensitized and challenged with ovalbumin, while the control group received saline using the same protocol. Twenty-four hours before the first challenge, control and OVA animals were further randomized into three subgroups to receive saline (SAL), BMDMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 39 publications
1
30
1
Order By: Relevance
“…Of these, 30 studies were selected for full text review, 19 of which met the inclusion criteria. Two studies were excluded because bone marrowederived mononuclear cells were used rather than stem cells [7,8] because soluble factors from bone marrow cells were used [5].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 30 studies were selected for full text review, 19 of which met the inclusion criteria. Two studies were excluded because bone marrowederived mononuclear cells were used rather than stem cells [7,8] because soluble factors from bone marrow cells were used [5].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, Abreu et al [7,8] have shown that bone marrow mononuclear cell administration before allergen challenge also reduced eosinophilic infiltration, Th2 cytokines, airway remodeling and airway hyperresponsiveness whether injected intravenously or intratracheally. With the use of MSCs treated with a cross-linker to prevent release of soluble factors, Goodwin et al [20] demonstrated that the effects of MSCs were not due to surface antigens either, but to soluble factors.…”
Section: Proposed Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the NI of the lines with the epithelial basal membrane is proportional to the airway area, the magnitude of bronchoconstriction (contraction index) was computed as contraction index = NI/√NP. 22 Lung morphometric analysis was performed in a blinded fashion.…”
Section: Lung Histologymentioning
confidence: 99%
“…In the ovalbumin asthma model, murine bone marrow-derived mononuclear cells, which were isolated using gradient centrifugation and administered intravenously, attenuated eosinophilic inflammation, airway remodelling, and physiologic parameters (105). These effects were independent of the route of administration (intravenous or intratracheal) (106). Next, her group compared their bone marrow-derived mononuclear cells to murine bone marrow-derived MSCs.…”
Section: Session 5: Careers In Stem Cells Cell Therapies and Lung Bmentioning
confidence: 99%